Synthesis and Characterization of Ion Pairs between Alkaline Metal Ions and Anionic Anti-Aromatic and Aromatic Hydrocarbons with π-Conjugated Central Seven- and Eight-Membered Rings - Jan Bloch (Molecules, 2020)
The synthesis, isolation and full characterization of ion pairs between alkaline metal ions (Li+, Na+, K+) and mono-anions and dianions obtained from 5H-dibenzo[a,d]cycloheptenyl (C15H11 = trop) is reported. According to Nuclear Magnetic Resonance (NMR) spectroscopy, single crystal X-ray analysis and Density Functional Theory (DFT) calculations, the trop‒ and trop2−• anions show anti-aromatic properties which are dependent on the counter cation M+ and solvent molecules serving as co-ligands. For comparison, the disodium and dipotassium salt of the dianion of dibenzo[a,e]cyclooctatetraene (C16H12 = dbcot) were prepared, which show classical aromatic character. A d8-Rh(I) complex of trop− was prepared and the structure shows a distortion of the C15H11 ligand into a conjugated 10π -benzo pentadienide unit—to which the Rh(I) center is coordinated—and an aromatic 6π electron benzo group which is non-coordinated. Electron transfer reactions between neutral and anionic trop and dbcot species show that the anti-aromatic compounds obtained from trop are significantly stronger reductants.